CAREER ADAPTABILITY IN VARIOUS THEORIES: REVIEW THROUGH MULTICULTURAL PERSPECTIVES - Kusyadi, Yudi (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
This paper intends to discuss the review of career adaptability in several different theoretical settings using a multicultural perspective. The scope of the discussion includes the definition, essence, aspect, and indicator of career adaptability in several theories. The methodology used is in the form of a literature review. This paper aims to provide benefits in providing descriptions of how career adaptability in several theories to gain a deeper understanding of the concept. The results obtained in the form of a review of the concept of ?career adaptability? using a multicultural perspective from three different theories derived from the career construction counselling approach and the social-cognitive counselling approach. Each theory has been reviewed from four dimensions, namely: definition, essence, aspects, and indicators.